Low dose radiation therapy, particularly with 0.5 gy, improves pain in degenerative joint disease of the fingers: Results of a retrospective analysis - Donaubauer, Anna-Jasmina; Zhou, Jianguo; Ott, Oliver J.; Putz, Florian; Fietkau, Rainer; Keilholz, Ludwig; Gaipl, Udo; Frey, Benjamin; Weissmann, Thomas (International Journal of Molecular Sciences, 2020)
Low-dose radiation therapy (LDRT) has been successfully established for decades as an alternative analgesic treatment option for patients suffering from chronic degenerative and inflammatory diseases. In this study, 483 patients were undergoing LDRT for degenerative joint disease of the fingers and thumb at the University Hospital Erlangen between 2004 and 2019. Radiotherapy was applied according to the German guidelines for LDRT. Several impact factors on therapeutic success, such as the age and gender, the number of affected fingers, the single and cumulative dose, as well as the number of series, were investigated. In summary, 70% of the patients showed an improvement of their pain following LDRT. No significant impact was found for the factors age, gender, the number of series or the cumulative dosage. Patients with an involvement of the thumb showed a significantly worse outcome compared to patients with an isolated affection of the fingers. In this cohort, patients receiving a single dose of 0.5 Gy reported a significantly better outcome than patients receiving 1.0 Gy, strongly suggesting a reduction in the total dose. In summary, LDRT is a good alternative treatment option for patients suffering from degenerative and inflammatory joint disease of the fingers.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Chronic degenerative and inflammatory diseases; Degenerative joint disease of the fingers; LDRT; Low-dose radiation therapy; Osteoarthritis; Subjective pain level